Mauprat - Sand, George, 1804-1876; Young, Stanley (Salt Lake City, UT : Project Gutenberg, 2006)
"Mauprat" by George Sand is a novel published in 1837. This Gothic romance follows Bernard Mauprat, a nobleman raised by violent kinsmen who becomes a brutalized outcast. When he helps his cousin Edmée escape captivity, he extracts a promise of marriage through threat. What follows is a gradual courtship that challenges traditional gender roles and questions women's education in society. Blending elements of "Beauty and the Beast" with social commentary, Sand crafts a story of transformation that culminates in a dramatic trial scene where love and redemption hang in the balance. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mauprat_(novel)
Release date is 2006-03-26
Produced by Dagny; John Bickers and David Widger
Keywords: Women's rights -- Fiction; Women -- France -- Fiction